2017
DOI: 10.1002/jcp.25994
|View full text |Cite
|
Sign up to set email alerts
|

Mild mitochondrial uncoupling induces HSL/ATGL‐independent lipolysis relying on a form of autophagy in 3T3‐L1 adipocytes

Abstract: Obesity is characterized by an excessive triacylglycerol accumulation in white adipocytes. Various mechanisms allowing the tight regulation of triacylglycerol storage and mobilization by lipid droplet-associated proteins as well as lipolytic enzymes have been identified. Increasing energy expenditure by inducing a mild uncoupling of mitochondria in adipocytes might represent a putative interesting anti-obesity strategy as it reduces the adipose tissue triacylglycerol content (limiting alterations caused by cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 100 publications
(161 reference statements)
3
17
0
Order By: Relevance
“…The previous study had also demonstrated that HSL/ATGL-independent lipolysis relies on the form of autophagy. 44 On the bases of these studies, it is suggested that PRMT4 may promote lipid droplet breakdown and the release of FFAs by activating autophagy. However, these possibilities require further research for their confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study had also demonstrated that HSL/ATGL-independent lipolysis relies on the form of autophagy. 44 On the bases of these studies, it is suggested that PRMT4 may promote lipid droplet breakdown and the release of FFAs by activating autophagy. However, these possibilities require further research for their confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the induction of OXPHOS uncoupling has been recognized as a possible therapeutic strategy for obesity 46,56 , neurodegeneration 57,58 , aging 59 , renal ischemia/reperfusion injury 60 , heart injury 61 and cancer 62,63 , well-known protonophore OXPHOS uncouplers exhibit a narrow therapeutic window 64 and off-target effects at other membranes, producing toxicity 3133 and limiting their potential clinical uses. In contrast to FCCP, FR58P1a does not depolarize the plasma membrane and induces a mild OXPHOS uncoupling, inducing mitochondrial NADH oxidation with sustained mitochondrial depolarization and a transient ATP decrease that activates AMPK in a Sirt1-dependent fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Although MTOR inhibition may be the main contributor to autophagy in BAT from hyperthyroid mice, it is possible that other upstream signalling pathways also contributed to MTOR inhibition. In particular, it is possible that UCP1-independent mitochondrial uncoupling also could have contributed to MTOR inhibition and/or autophagy, since mild mitochondrial uncoupling by FCCP induced autophagy in adipocytes [48]. In support for adipocytes treated with 10 nM T 3 for 0, 3, 6 and 24 h. Result represents mean ± SD (n = 6) where n represents number of independent experiments.…”
Section: T 3 Inhibits Mtor Activity By Amino Acid Catabolism and Sirtmentioning
confidence: 95%